2023
DOI: 10.3389/fpls.2023.1139757
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive review on patulin and Alternaria toxins in fruit and derived products

Abstract: Mycotoxins are toxic secondary metabolites produced by certain fungi, which can contaminate various food commodities, including fruits and their derived products. Patulin and Alternaria toxins are among the most commonly encountered mycotoxins in fruit and their derived products. In this review, the sources, toxicity, and regulations related to these mycotoxins, as well as their detection and mitigation strategies are widely discussed. Patulin is a mycotoxin produced mainly by the fungal genera Penicillium, As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 313 publications
0
8
0
Order By: Relevance
“…Patulin has attracted global attention because of the health risks it exacerbates. Indeed, this mycotoxin has mutagenic, neurotoxic, immunotoxic, genotoxic, and gastrointestinal effects in humans and animals [ 25 ]. Another secondary metabolite detected in our research was roquefortine C. This toxin was produced by 12 Penicillium species, including P. commune (3 strains), P. solitum , P. chrysogenum (2 strains), P. lanosocoeruleum (2 strains), and P. allii and Penicillium sp.…”
Section: Resultsmentioning
confidence: 99%
“…Patulin has attracted global attention because of the health risks it exacerbates. Indeed, this mycotoxin has mutagenic, neurotoxic, immunotoxic, genotoxic, and gastrointestinal effects in humans and animals [ 25 ]. Another secondary metabolite detected in our research was roquefortine C. This toxin was produced by 12 Penicillium species, including P. commune (3 strains), P. solitum , P. chrysogenum (2 strains), P. lanosocoeruleum (2 strains), and P. allii and Penicillium sp.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al [29] found that patulin was also detected in the tissue of citrus blue mold caused by P. digitatum. Bacha et al [30] found that the most common toxin in fruits and their derivatives is patulin produced by penicillium species. Patulin can also interact with other compounds in food and is responsible for the presence of patulin in rotten apples and apple products such as fruit juices, jams, and cider.…”
Section: Discussionmentioning
confidence: 99%
“…It can also lead to renal tumors, Balkan endemic nephropathy, and chronic interstitial nephropathy . Patulin is produced by Penicillium , Aspergillus , and Byssochlamys , while alternariol (AOH) and alternariol monomethyl ether (AME) are Alternaria toxins, produced by fungi of the Alternaria genus found in fruits and related products …”
Section: Recent Advancements In Food Toxin Detection Using Msmentioning
confidence: 99%